Ultrasound-assisted extraction of itraconazole from pellets: an efficient approach for the recovery of active pharmaceutical compounds from solid dosage forms - Ferreira, Patricia G.; Lima, Carolina G. S.; de Moraes, Marcela C.; da Silva, Fernando de C.; Futuro, Débora O.; Ferreira, Vitor F. (Frontiers in Analytical Science, 2024)
Itraconazole is a widely used broad-spectrum antifungal drug on a global scale. However, its poor water solubility necessitates the development of advanced formulations for its effective use. Currently, itraconazole is available commercially in capsule form, with pellets containing the active drug. The extraction of itraconazole from these granules is often required when developing new formulations. Extracting active pharmaceutical ingredients (APIs) from pellets is crucial in ensuring precise and consistent dosing when producing pharmaceutical dosage forms. Surprisingly, no existing methods for extracting itraconazole from pellets have been reported thus far. Therefore, this study aimed to develop and evaluate an efficient method for extracting this API from pellets. Two extraction methods were assessed: conventional Soxhlet extraction and ultrasound-assisted extraction. The results demonstrated that ultrasound-assisted extraction significantly outperformed the conventional method, yielding higher amounts of itraconazole with a high purity level of 96.8%.